The analysis of ICT needs on Chemistry learning in high school of North Aceh - Unaida, Ratna; Lukman, Isna Rezkia; Fakhrah, F (Universitas Malikussaleh, 2022)
This study aims to describe the analysis of ICT needs in chemical learning in North Aceh Regency High School. The methods used in this study use qualitative descriptive. This study was conducted at 43 high schools located in North Aceh Regency. The subjects in this study were all high school teachers in North Aceh Regency who numbered 86 teachers who taught chemistry subjects. The data collection techniques were observation, interview and questionnaire. The results showed that as many as 25 teachers (29%) did not use and utilize ICT in the learning process, this is due to the lack of facilities and infrastructure that support the availability of ICT devices such as insufficient and adequate information availability, the unavailability of adequate LCDs, the unavailability of computers/computer laboratories (computers are only available for school administration activities), and obstacles that are often experienced, namely the difficulty of internet access and Unstable electricity. A total of 21 teachers (24%) do not understand how to use ICT in learning. A total of 40 teachers (47%) already used and utilize ICT in the learning process. Such as the use of power point slides, learning videos, animated videos, the internet, email and social media.